Effect of 5-HTTLPR on current source density, connectivity, and topological properties of resting state EEG networks - Proshina, Ekaterina A.; Savostyanov, Alexander N.; Bocharov, Andrey V.; Knyazev, Gennady G. (Brain research, 2018)
•S-allele carriers have lower current source density in most frequency bands.•They have lower connectivity values.•They have lower smallworldness in theta, but higher in alpha band.•The latter may reflect a disbalance between emotional and cognitive processes. The S allele of serotonin transporter gene (5-HTTLPR) has been found to increase the risk of depression and other mental health problems, but some evidence suggests that S-allele carriers outperform subjects carrying the long allele in an array of cognitive tasks. Evidence linking this polymorphism with individual variation in electrophysiological properties of resting state brain networks is very limited. This study investigated the effect of 5-HTTLPR polymorphism on EEG current source density, connectivity, and topological properties of resting state networks. We collected genetic and resting state EEG data in 113 Caucasians. As compared to L-homozygotes, S-allele carriers showed lower current source density and connectivity in most frequency bands in areas overlapping with the default mode and emotion regulation regions. The analysis of graph-theoretical measures showed that S-allele carriers, as compared to L-homozygotes, have less optimal topological properties of brain networks in theta, but more optimal in alpha band. This dissociation may reflect the predisposition to emotional disorders, which is inherent to S-allele carriers, and, on the other hand, their superior functioning in some cognitive domains.